2022
DOI: 10.1002/jcsm.13044
|View full text |Cite
|
Sign up to set email alerts
|

Compartment‐specific effects of muscle strength on bone microarchitecture in women at high risk of osteoporosis

Abstract: Background It is well known that skeletal integrity is influenced by the musculature. Poor muscle strength (i.e. sarcopenia) is considered a major predictor of fragility fractures. While this observation appears particularly relevant for older women with increased risk of osteoporosis, there has been no comprehensive investigation to determine the influence of muscle performance on compartment-specific bone microarchitecture in multiple body regions. Methods We retrospectively analysed data from different musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…(27) Strong site-specific associations have also been observed been upper-and lower-limb muscle strength and bone structural parameters. (7,20) Thus, it has been suggested that both bone and muscle loss are biologically linked and the combined losses of these tissues in older adults may increase fracture risk. (19) However, our findings do not support a consistent interaction between bone and muscle on fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(27) Strong site-specific associations have also been observed been upper-and lower-limb muscle strength and bone structural parameters. (7,20) Thus, it has been suggested that both bone and muscle loss are biologically linked and the combined losses of these tissues in older adults may increase fracture risk. (19) However, our findings do not support a consistent interaction between bone and muscle on fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5) A recent review of preclinical and human work (6) suggests that bone and muscle loss during aging is underpinned by shared mechanisms relating to chemical and mechanical cross-talk. Considering mechanical interactions, a recent study (7) showed strong site-specific associations between grip strength and radial cortical bone and chair stand force and tibial cortical bone, measured by HR-pQCT. Indeed, it has been suggested that the joint loss of bone and muscle during aging, a concept known as osteosarcopenia (see reviews (8,9) ), may increase fracture risk in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 2 decades, peripheral quantitative computed tomography (pQCT) and high resolution peripheral quantitative computed tomography (HR-pQCT) have emerged as essential technologies for segmentation and quantification of bone, muscle and adipose tissue properties at the diaphyseal regions of the limbs. Segmentation of hard and soft tissues in pQCT and HR-pQCT imaging has been used to assess the effects of type-2 diabetes mellitus (T2DM) (Starr et al, 2018), osteoporosis (Simon et al, 2022) and osteoarthritis (Chen et al, 2018), to establish measures for characterizing sex-, ethnic-, site-, and age-related outcomes (Gabel et al, 2018), to study the effect of exercise on the muscle and fat cross-sectional areas (Rowe et al, 2019), and in studies of aging and age-related diseases (Chow et al, 2022;Liu et al, 2022). A challenge in pQCT-based segmentation is subject movement and the associated motion artifacts.…”
Section: Introductionmentioning
confidence: 99%